An expandable catheter loop coil for intravascular MRI in larger blood vessels - Homagk, Ann-Kathrin Verena; Umathum, Reiner; Korn, Matthias; Weber, Marc-André; Hallscheidt, Peter; Semmler, Wolfhard; Bock, Michael (Magnetic resonance in medicine, 2010)
The present study proposes a catheter system with an expandable coil etched on a polyimide foil. The catheter system combines the advantages of a small insertion diameter when the coil is rolled up in a protective carrier sheath with an increased signal-to-noise ratio (SNR) and penetration depth when the coil is pushed out. After imaging, the coil can be retracted into the sheath and folded back into the initial rolled-up configuration due to the tapered geometry of the carrier foil. The catheter system was tested on two healthy anesthetized pigs, including tracking and high-resolution intravascular imaging. To reduce artifacts in high-resolution images induced by catheter motion in the pulsatile blood flow, a motion-gating method was implemented that combines a flow-compensated two-dimensional fast low angle shot (FLASH) imaging sequence with the acquisition of projection data for retrospective gating. Using the projection data for motion detection, image SNR was increased by up to 500% over uncorrected images, and anatomic structures of 150 μm size could be differentiated in the aorta. Magn Reson Med, 2010. © 2009 Wiley-Liss, Inc.